1990
DOI: 10.1007/bf00315408
|View full text |Cite
|
Sign up to set email alerts
|

Liposome encapsulation improves efficacy of betamethasone dipropionate in atopic eczema but not in psoriasis vulgaris

Abstract: The effect of a liposomal preparation of beta-methasone dipropionate (0.039%, BDP) has been compared to that of a commercial propylene glycol-gel containing 0.064% BDP in a double-blind, randomized, paired trial lasting 14 d in 10 patients with atopic eczema and 10 patients with psoriasis vulgaris. In eczema, the liposome preparation tended to reduce erythema and scaling more than the conventional gel, the difference in the latter parameter being significant on Day 7. There was greater improvement of psoriasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(40 citation statements)
references
References 13 publications
1
38
0
1
Order By: Relevance
“…Although liposomal drug gels caused no adverse symptoms from the 4th week of treatment, some symptoms were observed in the initial phase of treatment. This agrees with the findings of Korting et al [13] that liposomal formulation of betamethasone reduced erythema and scaling more than a conventional gel and did so more rapidly. This can be further correlated to less free drug being available with liposomal encapsulation [14], which produced better results and thus improved patient compliance to a larger extent.…”
Section: Adverse Symptoms Of Therapysupporting
confidence: 83%
“…Although liposomal drug gels caused no adverse symptoms from the 4th week of treatment, some symptoms were observed in the initial phase of treatment. This agrees with the findings of Korting et al [13] that liposomal formulation of betamethasone reduced erythema and scaling more than a conventional gel and did so more rapidly. This can be further correlated to less free drug being available with liposomal encapsulation [14], which produced better results and thus improved patient compliance to a larger extent.…”
Section: Adverse Symptoms Of Therapysupporting
confidence: 83%
“…In addition, it was shown that vesicles can penetrate a ruptured or diseased SC as in case of eczema but cannot transport a skin with psoriasis or hyperkeratosis conditions [31]. On the other hand, Zellmer et al [32], and Korting et al [33] indicated that there was no evidence of intact liposomal carrier penetration after skin application of liposomes made from DMPC "1,2-dimyristoyl-sn-glycero-3-phosphocholine" or soy-lecithin.…”
Section: Intact Vesicular Penetration Mechanism Into the Skinmentioning
confidence: 99%
“…Korting et al [61] compared the efficacy of betamethasone dipropionate encapsulated in liposomes and cream. The liposomes were prepared with egg lecithine and incorporated in a polyacrylate gel.…”
Section: Formulations Of Tcmentioning
confidence: 99%